Eradication Of Poverty And Welfare In An Islamic Perspective - Nanang Yusroni; Mochamad Purnomo; Umar Chadhiq; Nurul Komaryatin (Jurnal Ekonomika dan Bisnis, 2022)
A B S T R A C T Islam is a religion, and religion is closely linked to belief. Furthermore beliefs are emotional, and therefore need islamic and non-Muslim relations to be well regulated. The difference between rich and poor always brings chaos in society and to overcome it, the verses of the Qur'an also concern the relationship of rich and poor. The economic severity of our country over the years has led to poverty, which has swelled and increased. Swells and rising poverty are evident with the increasing number of unemployment, Unemployment is increasingly large children and adolescents out of school, homeless, low quality, violent behavior and efficacy and imperviousness. That is how it is, poverty has attracted to disbelief, low temperament and criminality that harms society. Thus, poverty is one of those social problems that can be viewed as another source of social problems.